Journey to Juno - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2013)
On the planet Nebulon in 2120, Zack joins his school's Explorer's Club and visits Juno, a planet made of crystals, but he is less than thrilled when he is partnered with the class bully.